Development of the Concept of a Collection of Dresses from Khonatlas Fabric (Eurasian Journal of Engineering and Technology, 2022)
In the problems of modern design, the problem of creative concept (the main idea, the merits and tasks of design, the spiritual path) occupies a central place. Conceptuality is a general creative instruction that underpins the essence of a project culture. This article is about the development of the concept of a collection of dresses made of khan satin fabric.